DISCOURSE ANALYSIS OF THE QUOTIDIAN SONG: “SOY MUCHACHO PROVINCIANO” (I AM A PROVINCIAL YOUNG MAN) - Rojas Dominguez, Leonor (2013)
We often wonder what is the impact generated by the lyrics of popular songs fromthe “chicha” gender in the collective imagination. This paper will analyze thediscourse of the lyrics of the song Soy muchacho provinciano, which was performed by the renowned singer of popular music Lorenzo Palacios Quispe better knownwith the pseudonym of Chacalón.